(untitled) (Journal of Comparative Social Work, 2017)
To which extent do dysfunctional political systems lead to everyday challenges for social workers? Moreover, how do social workers benefit from working in well-ordered democracies? The purpose of this paper is to gain insights into how the interplay between the political context and social work actually operates. Our main question is: How do accountability and state capacity levels affect daily social work? This interplay frequently becomes associated with levels of democracy and redistribution. We also draw attention to how social workers’ are dependent on the capacity of the state to implement policies. We compare social work and the political and legal contexts in two widely different polities – Norway and Bolivia. Our primary findings indicate that the effects of generally unfavourable political conditions permeate the possibilities for effective social work in previously unforeseen ways. Coordination problems, clientelism and political rivalry lead to everyday challenges on the ground, as many problems seem to reflect the overall institutional system and political culture. In well-ordered political systems, these problems are hardly an issue. In our concluding discussion, we address how the nature of the institutional system and political culture apparently might call for a differentiated approach towards reform strategies. For instance, progressive politicians, citizens and social workers advocating a policy transfer could face severe hindrances in polities, thus comprising weak state capacities.